Minor Groove Binder-Conjugated DNA Probes for Quantitative DNA Detection by Hybridization-Triggered Fluorescence. (April 2002) - Afonina, I.A.; Reed, M.W.; Lusby, E.; Shishkina, I.G.; Belousov, Y.S.
Here we describe the properties of a novel class of oligonucleotide probes capable of sensitive hybridization-triggered fluorescence. These fluorogenic probes, known commercially as MGB Eclipse™ probes, are characterized by having a conjugated minor groove binder (MGB) ligand at the 5′-end and a fluorophore at the 3′-end. Additionally, they have an efficient quencher moiety at the 5′-end that is useful with a wide variety of fluorescent dyes. Fluorescence of the single-stranded MGB Eclipse™ probe is efficiently quenched by the interaction of the terminal dye and quencher groups when not hybridized. Upon hybridization to a complementary target, the MGB molecule folds into duplex and hyper-stabilizes it, allowing the use of shorter, more specific probe sequences. The 5′-MGB-quencher group also prevents nuclease digestion by Taq DNA polymerase during PCR. Because of the hybridization-triggered fluorescence and the excellent specificity imparted by the MGB, these 5′-MGB Eclipse probes have great versatility for real-time PCR applications. The high sensitivity and specificity are illustrated using single nucleotide polymorphism detection, viral load determination, and gene expression analysis.